OCEB 2 certification guide business process management, fundamental level - Weilkiens, Tim; Weiss, Christian; Grass, Andrea R.; Duggen, Kim Nena (Morgan Kaufmann, 2016)
OCEB-2 Certification Guide, Second Edition has been updated to cover the new version 2 of the BPMN standard and delivers expert insight into BPM from one of the developers of the OCEB Fundamental exam, offering full coverage of the exam material for both the business and technical tracks. The first study guide to prepare candidates to take and pass the OCEB Fundamental exam, it explains and builds on basic concepts, focusing on key areas and testing knowledge of all critical topics with sample questions and detailed answers. Suitable for practitioners and those newer to the field, this book provides a solid grounding in business process management based on the authors' own extensive BPM consulting experience.Completely updated with the latest material that one needs to pass the OCEB-2 and BPMN CertificationIncludes sample test questions in each chapter with all answers in the appendixExpert authors provide a solid overview of business process management (BPM)
Keywords: BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Business consultants / Certification; Electronic data processing personnel / Certification; Industrial management / Examinations; Business consultants -- Certification; Electronic data processing personnel -- Certification; Industrial management -- Examinations -- Study guides; Management information systems -- Examinations -- Study guides